ChemInform Abstract: Mn(III)‐Based Reaction of Alkenes with Quinolinones. Formation of Peroxyquinolinones and Quinoline‐Related Derivatives. Issue 33 (19th August 2014) - Nishino, Hiroshi; Kumabe, Ryoukou; Hamada, Ryoichi; Yakut, Mehtap
Abstract The Mn(III)‐promoted aerobic oxidation of alkenes in the presence of 4‐hydroxyquinolin‐2(1H)‐ones under different reaction conditions is examined resulting in the formation of various types of quinoline derivatives.